Cycloparaphenylene and their radicals anchored to a metal−organic framework. (September 2022) - Jiang, Z.; Duan, W.; Lin, W.; Yang, L.; Wu, Z.; Wang, J.; Wang, S.; Du, P.; Li, Q.
Abstract: Cycloparaphenylene (CPP) shows modulated photophysical and electronic properties due to its strained structure and radially oriented π-electron system. Incorporation of CPP into metal-organic frameworks (MOFs) could transfer its extensive properties in solution to porous solids. Moreover, with the unique arrangement of the macrocycles and their interactions with the framework, emerging characteristics are anticipated. As an example of "robust dynamics",  we synthesized the first MOF structure (FDM-1001) with CPP precisely anchored to the ordered framework by employing a [8]CPP-containing linear dicarboxylate linker. Metric relationship between the dynamic macrocycles and the robust backbone creates ideal π-π interactions between them, which leads to an essentially directional arrangement of [8]CPP in the three-dimensional space. Furthermore, the MOF with [8]CPP could be successfully oxidized to generate an infinite array of radicals that show enhanced air stability compared to its molecular analogue. Highlights: [8]Cycloparaphenylene is successfully incorporated into a metal−organic framework FDM-1001. Directional arrangement of cycloparaphenylene nanohoops in the open framework is proposed. The nanohoops in the framework can be converted into persistent radicals by oxidation. Graphical abstract: Image 1